Calidad fisicoquímica y microbiológica de glicerina materia prima comercializadas en el mercado nacional - Ore Cruz, Roberth Yon (2019)
The purpose of this report is to evaluate the physicochemical and microbiological quality of glycerin raw material marketed in the national market; for which, samples of 03 lots each from different suppliers were obtained, which were coded with the letters A, B and C respectively. Results of the physicochemical tests were that is a transparent, sirupous, and colorless liquid, with characteristic odor not pungent or unpleasant, with a sweet taste. In the identification test absorbance was 0,480. Turbidity of the sample was not bigger than the standard, no more than 10 ppm in the chloride test and no more than 20 ppm in the sulfate test. The incineration residue was 0,003%. The organic impurity tests at the limit of chlorinated compounds was not more than 30 ppm of chlorine and in the fatty acid and esters test, the O,5N NaOH was 0,5 mL The specific weight of the analyzed samples was 1,2602. The water determination test gave us a result of 0, 06 % and the glycerol titration was 99,93% with respect to the anhydrous substance. The results of the microbiological tests evaluated were: <10 CFU for total aerobic microorganism count and filamentous fungal and yeast count based on laboratory analytical technique according to the United States Pharmacopeia (USP 42). The physicochemical and microbiological results of glycerin raw material are in accordance with the technical specifications established in the United States Pharmacopoeia (USP 42). Keywords: